A new species of Biffarius manning & felder, 1991 (decapoda: axiidea: callianassidae) from the intertidal coast of northeastern Brazil - Hernáez, Patricio [UNESP]; Miranda, Marcel S.; Tavares, Marcos (Magnolia Press, 2020)
A new species of intertidal ghost shrimp, Biffarius botterae, is described from Maranhão and Ceará in northeastern Brazilian coast. Diagnostic features of the new species include: (1) antennular peduncle shorter than antennal peduncle; (2) male major cheliped massive; (3) male pleopod 2 uniramous, vestigial; (4) uropodal endopod widening distally, inner lateral margin convex; and (5) anterodorsal plate of uropodal exopod absent. Biffarius Manning & Felder, 1991, now consists of four species: B. biformis (Biffar, 1971), B. botterae sp. nov., B. delicatulus Rodrigues & Manning, 1992, and B. limosus (Poore, 1975). A key to the species of Biffarius is provided.
Keywords: Australia; Brazil; Burrowing shrimps; Fragillianassa; Intertidal zone; Neocallichirus